Uncovering a Novel Role of ROR1 in the Epigenetic Regulation of Tumor Suppressor Gene CREB3L1 in Triple-Negative Breast Cancer Cells - Victoria L. Reed; Eric Lalu; Leena Yoon; Norman Fultang; Bela Peethambaran (Biomolecules)
A characteristic of triple-negative breast cancer (TNBC) is the epigenetic regulation of tumor suppressor genes, leading to TNBC heterogeneity and treatment resistance in patients. TNBC exhibits high methylation rates, leading to the silencing of numerous tumor suppressor genes. DNA methyltransferase inhibitors (DNMTis) have shown limited clinical efficacy in TNBC treatment. This study aims to uncover a target that could be used to reverse the epigenetic silencing of tumor suppressor genes in TNBC. The Western blot analysis demonstrated that ROR1 knockdown, an oncofetal gene, reduced DNMT3A and DNMT3B protein expression in the TNBC cell lines MDA-MB-231 and HCC1806, as well as a non-malignant breast cell line, MCF10A. The reduced representation bisulfite sequencing (RRBS) analysis identified differential methylation of CREB3L1 when ROR1 is knocked down in TNBC cell lines. CREB3L1 is a transcription factor that plays tumor-suppressive roles in TNBC and is commonly epigenetically silenced in patients. This study shows that ROR1 requires pSTAT3 activation to upregulate DNMT3A and DNMT3B expression to induce CREB3L1 epigenetic silencing in TNBC. ROR1 knockdown resulted in the re-expression of CREB3L1 in TNBC cells. The data provide evidence that ROR1 inhibition, in combination with DNMTis, could enhance patient outcomes as a therapeutic approach for TNBC.